PENGUSULAN PEMBANGUNAN ‘RUMAH SUSUN SEDERHANA’ DI UNIVERSITAS KRISTEN INDONESIA TORAJA - Topayung, Semuel Linggi (Jurnal PKM Setiadharma, 2024)
This article is the result of a proposal for the construction of Simple Apartments at the Indonesian Christian University of Toraja as a solution to address the issue of limited housing for students and staff. This proposal is motivated by the high demand for affordable and nearby housing, as well as the limited land around the university. The Simple Apartments are expected to provide adequate, safe, and comfortable living facilities at an affordable cost. This development is also designed to support academic and non-academic activities and improve the quality of life for its residents. Through this approach, the Indonesian Christian University of Toraja can make a positive contribution to the well-being of the campus and surrounding community. This study outlines the planning, design, and feasibility analysis of the construction project, as well as identifies potential challenges and solutions that can be implemented. It is hoped that this proposal can serve as a model for other educational institutions in providing quality housing facilities for students and staff.